Relationship between Antenatal Maternal Neutrophil-to-Lymphocyte Ratio and Early Onset Neonatal Sepsis in Preterm Neonates - Thitiphan Chayawongrungreung; Jiraporn Luengmettakul; Aungsumalin Srilar (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To determine the relationship between maternal neutrophil to lymphocyte ratio (NLR) and early onset neonatal sepsis (EONS) in preterm neonates.Materials and Methods: Between 2012 to 2016, a total of 485 cases of preterm delivery were retrospectively reviewed. Study group consisted of 97 neonates diagnosed with EONS and other 388 without EONS were randomly selected as a comparison group (1:4 ratio). Data were extracted from medical records, including baseline characteristics, obstetric and delivery data. Maternal NLR was calculated from laboratory results within 72 hours prior to delivery. Results: Neonates with EONS were significantly more likely to deliver at < 34 weeks (p < 0.001), had preterm premature rupture of membranes (p = 0.043), and had maternal fever (p = 0.016). White blood cell and neutrophil counts were significantly higher in EONS group while lymphocyte counts were comparable. Median NLR was significantly higher in EONS group (4.7 vs. 4.1, p = 0.005). NLR of > 5 significantly increased the risk of EONS (26.8% vs. 16.4%, p = 0.007). Logistic regression analysis showed that delivery at < 34 weeks and maternal fever were independently associated with EONS (adjusted odds ratio (ORs) 11.5, 95% confidence interval (CI) 6.7-19.7, and 3.4, 95% CI 1.1-11.3, respectively). Subgroup analysis showed that NLR of ≥ 5 independently increased the risk of EONS in those delivered at < 34 weeks (adjusted ORs 3.5, 95% CI 1.4-9.1) and maternal fever independently increased the risk of EONS in those delivered at ≥ 34 weeks (adjusted ORs 6.1, 95% CI 1.8-20.3).Conclusion: Maternal NLR was significantly associated with EONS in preterm neonates, especially those delivered at < 34 weeks.